Penerapan Prinsip Ekonomi Islam dalam Sistem Ekonomi Kontemporer - Siti Hanifah; Mistia Sofiyana; Tias Nursyafa'ah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article aims to analyze the relevance and implementation of Islamic economic principles within the context of a contemporary economic system dominated by capitalist paradigms. The background of this research stems from the global reality marked by wealth distribution inequality, moral crises in business, and social injustices resulting from profit-oriented economic systems. This study employs a qualitative approach using a literature review method, analyzing scholarly works, official institutional reports, and academic studies related to Islamic economics and modern economic challenges. The findings indicate that Islamic economic principles such as social justice, equitable wealth distribution, and the prohibition of riba (usury), gharar (excessive uncertainty), and maysir (gambling) hold strong applicative value in addressing various contemporary economic issues. Concrete implementations of these principles can be observed in the development of Islamic financial systems, digital zakat (almsgiving), productive waqf (endowments), and increasingly innovative and technology-responsive Islamic banking services. The discussion also reveals that Islamic economics can serve as an ethical and sustainable alternative to capitalism and socialism, particularly in terms of distributive justice and economic stability. Despite facing challenges in literacy, regulation, and technological infrastructure, Islamic economics has significant growth potential through collaboration among academics, practitioners, and policymakers. The conclusion of this study affirms that Islamic economic principles can serve as a transformative solution for the global economic system if applied adaptively, innovatively, and inclusively.